Evaluation of Oxidation – Antioxidation Balance in Sera of Patients with Acute Hepatitis Virus Type C. - Jasim, Rasha H. (Science Journal of University of Zakho, 2013)
Aim of the present study has to focused on the possible relationship between serum malondialdehyde level, an index of lipid peroxidation, and ceruloplasmin levels, as protective agent against lipid peroxidation, in hepatitis C virus. A group of 31 hepatitis virus type C patients were enrolled in the study, while; control group consisted of 25 healthy subjects. In the present study, total proteins (g/L), malondialdehyde (µM), ceruloplasmin oxidase activity (U/L) and ceruloplasmin concentration (g/L) were measured in sera samples of patients with hepatitis C virus as well as in the healthy controls.
Keywords: lipid peroxidation; malondialdehyde; ceruloplasmin